Hyperporous‐Carbon‐Supported Nonprecious Metal Electrocatalysts for the Oxygen Reduction Reaction. Issue 18 (1st August 2018) - Zhai, Tian‐Long; Xuan, Cuijuan; Xu, Jincheng; Ban, Li; Cheng, Zhiming; Wang, Shaolei; Wang, Deli; Tan, Bien; Zhang, Chun
Abstract: Highly porous carbonaceous nonprecious metal catalysts for the oxygen reduction reaction are prepared by carbonization of low‐cost metalloporphyrin‐based hyper‐crosslinked polymers (MPH‐X). With high surface area (2768 m 2 g −1 ), hierarchical porous structure, and high metal loading (9.97 wt %), the obtained hyperporous carbon MPH‐Fe/C catalyst exhibits high oxygen reduction reaction (ORR) activity with a half‐wave potential (0.816 V) that is comparable to the 0.819 V of commercial Pt/C. Stability tests reveal that MPH‐Fe/C also exhibits outstanding long‐term durability and methanol tolerance. Our findings may offer an alternative approach to produce nonprecious metal ORR catalysts on a large scale owing to the low‐cost MPH‐X precursors with diverse metal types. Abstract : Hyperporous carbon‐based nonprecious metal catalyst, MPH‐Fe/C, from a low‐cost metalloporphyrin‐based hyper‐crosslinked polymer, with high surface area, hierarchical pores, and high metal loading, exhibits excellent electrocatalytic performance for the oxygen reduction reaction, which is comparable to commercial Pt/C.